Aneurysmal bone cyst of the calcaneus: An unusual presentation (Indian Journal of Case Reports, 2021)
Aneurysmal bone cysts (ABCs) are vascular bony lesions that are benign, expansile, and locally destructive. The lesion may arise as a primary lesion (65%) or secondary to an underlying lesion (giant cell tumor, osteosarcoma, chondroblastoma, fibrous dysplasia, angioma, and others). The calcaneus is an uncommon location for ABC, accounting only for 1.6% of the cases. Reported is a case of a 21-year-old male patient who presented with chronic pain in his left heel from the past 5 months that got worse and used to aggravate on walking. The magnetic resonance imaging of the calcaneus showed a well-defined multiloculated, expansile cystic lesion in the medullary cavity causing adjacent cortical thinning with intralesional hyperintense septae and fluid level components. On clinicoradiopathological correlation, the lesion was diagnosed as an ABC. Hereby, we report a case of ABC of the calcaneus which is an uncommon presentation.